2019
DOI: 10.1177/2055207619890476
|View full text |Cite
|
Sign up to set email alerts
|

Responding to depression-related Imgur posts: A content analysis of social support and non-bona fide features in user-generated comments

Abstract: ObjectivesA growing body of health communication scholarship has explored the utility of social media platforms for eliciting social support, although much of this scholarship has focused on Facebook and Twitter. This study contributes to this body of research by identifying support in comments submitted to depression-related Imgur posts. Furthermore, the use of non-bona fide linguistic features (e.g. humor, sarcasm, and irony) is documented for comparison with supportive elements.MethodsA content analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…While reassuring support emerged more prominently than empathic and informational support in both Imgur and YouTube comments (Hale et al, 2018), this support type has been largely excluded from previous online cancer-related social support research (see Rains et al, 2015), and thus the relative prevalence of this support type is difficult to assess across studies. In addition, the findings of this study differ notably from a previous analysis of depression-related Imgur posts (Hale, 2019), where reassuring support emerged at a similar frequency to empathic and informational support (and lower levels than that found here), followed by tangible support. Considered together, these results agree with the propositions of optimal matching theory (Cutrona & Russell, 1990; Rains et al, 2015), as stressor characteristics (i.e., cancer versus depression) seem to affect the provision of different forms of support more than the platforms through which support is sought and provided.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While reassuring support emerged more prominently than empathic and informational support in both Imgur and YouTube comments (Hale et al, 2018), this support type has been largely excluded from previous online cancer-related social support research (see Rains et al, 2015), and thus the relative prevalence of this support type is difficult to assess across studies. In addition, the findings of this study differ notably from a previous analysis of depression-related Imgur posts (Hale, 2019), where reassuring support emerged at a similar frequency to empathic and informational support (and lower levels than that found here), followed by tangible support. Considered together, these results agree with the propositions of optimal matching theory (Cutrona & Russell, 1990; Rains et al, 2015), as stressor characteristics (i.e., cancer versus depression) seem to affect the provision of different forms of support more than the platforms through which support is sought and provided.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, previous analyses of Imgur content indicate that humor is commonly utilized in this context (Hale, 2017, 2019; Mikal et al, 2014). B. J. Hale (2019) found that non-bona fide linguistic features (e.g., humor, irony, and sarcasm) frequently manifested but rarely coincided with support in comments responding to Imgur posts about depression.…”
Section: Narrativementioning
confidence: 88%
See 2 more Smart Citations
“… 20 Therefore, online social support empowers depression sufferers, facilitating the development of a sense of self-determination. 5 , 24 …”
Section: Literature Reviewmentioning
confidence: 99%